Recreation ecology research in China’s protected areas: progress and prospect - Linsheng Zhong (Taylor & Francis Group, 2020)
As a type of tourist destination, Protected Areas (PAs) have been the focus of recreation ecology research since their establishment. The contradiction between recreation and ecological protection of PAs in China is more prominent than in other countries because of China’s large population density and complex PA management system. Thus, a review of related research is urgent for promoting sustainable tourism development of PAs in China. Combining quantitative analysis with a literature review, this study analyzed the historical development process and current research topics of recreation ecology in China’s PAs, focusing on the impacts of tourism on the natural environment, environmental management of tourism, and the development of different types of sustainable tourism in PAs. Overall, the research gaps are as follows: (1) studies on impact mechanism of tourism based on long-term monitoring are lacking; (2) the existence of numerous local communities in most of the PAs in China is usually ignored; (3) insufficient attention has been paid to the impacts of tourism infrastructure construction; (4) assessments of sustainable PA tourism are lacking. Correspondingly, this paper presents implications for future research and serves as a reference for PA tourism management in other countries.